LINGUOCULTURAL STUDY OF LINGUISTIC UNITS OF EXPRESSING SMELL IN ENGLISH AND UZBEK LANGUAGES - Sevara Khusanova (“ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI” MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2024)
Smell, as one of the five primary senses, holds a unique position in human perception and language. Linguistic expressions related to smell often reflect cultural values, social practices, and environmental realities. This article investigates the linguocultural features of linguistic units expressing smell in English and Uzbek. By analyzing lexical, semantic, and pragmatic aspects, the study reveals how smell-related expressions are shaped by the cultural and environmental contexts of these languages.